Kajian Penggunaan Bahasa Baku dalam Mewujudkan Komunikasi Efektif Awak Sarana Prasarana Melayani Perjalanan Kereta Api - Nyoto Setyo Marsusiadi, Edi; Wiarco, Yuwono; Meilia Wijayanti, Lisma; Iswanto, Ary Putra (LP. Ma'arif Janggan Magetan, 2023)
This study aims to describe the use of standard language in realizing effective communication between train facilities and infrastructure crews in carrying out their duties and functions for the creation of professional rail transportation mode services. Qualitative descriptive research methods that describe sociolinguistic conditions in the field of railway transport operators, as far as the observed knowledge that communication is used by the crew of facilities and infrastructure in carrying out their duties Observation, interview, and documentation techniques are carried out to determine the ability to use communication standards in the form of standard language and the implementation of effective communication of facilities and infrastructure crews in serving train travel Engineering Data analysis through the stages of reduction, presentation of data and drawing conclusions. The results of this study illustrate that good and correct mastery of Indonesian still needs to be improved and the use of standard language in train facilities and infrastructure crews still has limitations on the ability to use standard and non-standard types of words, both functionally the variety of standard language and standard sentence requirements. The goal of effective communication can be realized if between the communicator / sender of the message and the communicant / receiver of the message can carry out the message conveyed correctly without having to follow a standardized conversation pattern, although sometimes it does not follow the conversation pattern or recommended communication procedures following the technical guidance guidelines contained in the Standard Operating Procedure (SOP).